Two Distinctly Localized P-Type ATPases Collaborate to Maintain Organelle Homeostasis Required for Glycoprotein Processing and Quality Control - Vashist, Shilpa (The American Society for Cell Biology, 2002)
Membrane transporter proteins are essential for the maintenance of cellular ion homeostasis. In the secretory pathway, the P-type ATPase family of transporters is found in every compartment and the plasma membrane. Here, we report the identification of COD1/SPF1 (control of HMG-CoA reductase degradation/SPF1) through genetic strategies intended to uncover genes involved in protein maturation and endoplasmic reticulum (ER)-associated degradation (ERAD), a quality control pathway that rids misfolded proteins. Cod1p is a putative ER P-type ATPase whose expression is regulated by the unfolded protein response, a stress-inducible pathway used to monitor and maintain ER homeostasis. COD1 mutants activate the unfolded protein response and are defective in a variety of functions apart from ERAD, which further support a homeostatic role. COD1 mutants display phenotypes similar to strains lacking Pmr1p, a Ca(2+)/Mn(2+) pump that resides in the medial-Golgi. Because of its localization, the previously reported role of PMR1 in ERAD was somewhat enigmatic. A clue to their respective roles came from observations that the two genes are not generally required for ERAD. We show that the specificity is rooted in a requirement for both genes in protein-linked oligosaccharide trimming, a requisite ER modification in the degradation of some misfolded glycoproteins. Furthermore, Cod1p, like Pmr1p, is also needed for the outer chain modification of carbohydrates in the Golgi apparatus despite its ER localization. In strains deleted of both genes, these activities are nearly abolished. The presence of either protein alone, however, can support partial function for both compartments. Taken together, our results reveal an interdependent relationship between two P-type ATPases to maintain homeostasis of the organelles where they reside.